Ex. 7 va roggg !!! Imi trebuie pntr maine!
Anexe:
Răspunsuri la întrebare
Răspuns de
0
1+{2×[3+(a-4)×5]:6}×7=8
2×[3+(a-4)×5]:6 =(8-1):7
2×[3+(a-4)×5]:6=1
3+(a-4)×5=(1×6)÷2
3+(a-4)×5=3
(a-4)×5=3-3
a-4=0×5
a-4= 0
a=4
2×[3+(a-4)×5]:6 =(8-1):7
2×[3+(a-4)×5]:6=1
3+(a-4)×5=(1×6)÷2
3+(a-4)×5=3
(a-4)×5=3-3
a-4=0×5
a-4= 0
a=4
Alte întrebări interesante
Matematică,
8 ani în urmă
Franceza,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Fizică,
9 ani în urmă
Limba română,
9 ani în urmă